G/R 241 Polymorphism of Intercellular Adhesion Molecule 1 ( ICAM-1 ) Is Associated with Fuchs Uveitis - Cimino, Luca; Boiardi, Luigi; Aldigeri, Raffaella; Casali, Bruno; Nicoli, Davide; Farnetti, Enrico; Salvarani, Carlo; Cirone, Daniele; Martino, Liberatina De; Pupino, Alessandro; Cappuccini, Luca (Investigative ophthalmology & visual science, 2010)
To investigate potential associations of the ICAM-1 gene polymorphisms and Fuchs uveitis in a cohort of Italian patients. Seventy-one consecutive Italian patients affected by Fuchs uveitis were observed at the Ocular Immunology Unit, Arcispedale S. Maria Nuova (Reggio Emilia, Italy) from 2002 to 2008. Two hundred twenty-six healthy Italian blood donors from the same geographic area were selected as the control group. All Fuchs uveitis patients and control subjects were genotyped by polymerase chain reaction (PCR) and allele-specific oligonucleotide techniques for ICAM-1 polymorphisms at codon 241 (exon 4). The frequency of the ICAM-1 G/R 241 polymorphism was significantly higher in Fuchs uveitis than in the control subjects (16.9% vs. 5.8%; P=0.006, Pcorr=0.012; odds ratio, 3.3; 95% confidence interval, 1.4-7.7). No significant association between clinical features and ICAM-1 polymorphisms was found. This study demonstrates for the first time that the ICAM-1 G/R 241 polymorphism may represent a candidate gene for Fuchs uveitis susceptibility.